2019
DOI: 10.3389/fenrg.2019.00129
|View full text |Cite
|
Sign up to set email alerts
|

Gasifier, Solid Oxide Fuel Cell Integrated Systems for Energy Production From Wet Biomass

Abstract: Nowadays, there is worldwide interest in diversifying energy supply. In this regard, biomass is the best possible renewable organic substitute for fossil fuels. In particular, the energy content of very wet biomass, recovered with appropriate technology, could potentially be used for power generation. In addition to power generation, this technology would represent a sanitary option to improve the quality of public health and the environment. Supercritical water gasification (SCWG) is a technology applied for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The feedstock includes coal, biomass, waste materials such as municipal solid waste (MSW), sewage sludge, and other waste. It should be noted that due to the anticipated 70% rapid increase in the global waste generation between the year 2016 and 2050, gasification of waste materials is becoming a key technology interest . Apart from thermal applications, the product gas known as “syngas” from gasification can be utilized in various applications, such as fuelling an internal combustion (IC) engine, , gas turbine, and integrated gasification combined cycle for power generation; as a feed for Fischer–Tropsch/Alcohol synthesis reactors, synthetic natural gas, and hydrogen; and in advanced technologies like solid oxide fuel cells. , Several reactor configurations are available for gasification, including fixed bed, fluidized bed, entrained bed, and others, each with specific preferences for process conditions. By selecting the appropriate reactor configuration, the required syngas composition and conversion rates can be achieved to meet the specific needs of a particular application.…”
Section: Introductionmentioning
confidence: 99%
“…The feedstock includes coal, biomass, waste materials such as municipal solid waste (MSW), sewage sludge, and other waste. It should be noted that due to the anticipated 70% rapid increase in the global waste generation between the year 2016 and 2050, gasification of waste materials is becoming a key technology interest . Apart from thermal applications, the product gas known as “syngas” from gasification can be utilized in various applications, such as fuelling an internal combustion (IC) engine, , gas turbine, and integrated gasification combined cycle for power generation; as a feed for Fischer–Tropsch/Alcohol synthesis reactors, synthetic natural gas, and hydrogen; and in advanced technologies like solid oxide fuel cells. , Several reactor configurations are available for gasification, including fixed bed, fluidized bed, entrained bed, and others, each with specific preferences for process conditions. By selecting the appropriate reactor configuration, the required syngas composition and conversion rates can be achieved to meet the specific needs of a particular application.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Taufiq et al, [14] conducted a simulation of a power generation system that combined a coal gasification system, steam turbine system, gas turbine system, and fuel cell system, and the simulation results indicated an efficiency of 46.35 to 60.32%. Recalde et al, [15] performed a combined power plant simulation with a supercritical water gasification system and a SOFC using Aspen Plus. The simulation results showed that the resulting efficiency was around 50 to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Developing clean and efficient renewable energy sources are urgently required. Biomass fuels are considered the best renewable organic alternative to fossil fuels because of their extremely low sulfur content and renewable characteristics (Recalde et al, 2019;Wang et al, 2021). Lvxin fast-growing grass (hereafter referred to as the "fast-growing grass") is a fast-growing plant developed by Prof. Lei Xuejun (Lei, 2015) by hybridizing seven different varieties Lvxin grass.…”
Section: Introductionmentioning
confidence: 99%